Uncovering Profitability Drivers: The Effect of Green Accounting, Good Corporate Governance, and Firm Size in Coal Industry Listed on Indonesia Stock Exchange (2019 – 2023) - Muhammad Hanif Taufik; Galuh Tresna Murti (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Profitability refers to a company’s aptitude for deriving earnings from its operational undertakings and the judicious stewardship of its assets. This dimension illustrates the extent to which a firm utilizes its resources efficiently and reflects its success, competitiveness, and productivity within the industry. The objective of this inquiry is to scrutinize how green accounting, proxied by environmental performance (X1), good corporate governance embodied by the board of directors (X2), independent commissioners (X3), audit committee (X4), and firm size (X5), exerts an influence on profitability (ROA) (Y) among coal enterprises enumerated on the Indonesia Stock Exchange from 2019 to 2023. This study adopts a quantitative approach employing secondary data drawn from corporate annual disclosures. A purposive sampling technique was utilized to designate eleven firms, culminating in 55 observational data points. The independent variables (X) and the dependent variable (Y) were analyzed through panel data regression procedures. The findings unveil that environmental performance, board of directors, independent commissioners, audit committee, and firm size collectively impart an impact on profitability. Nevertheless, under partial scrutiny, solely firm size exerts a positive effect on profitability, whereas the remaining variables do not manifest significant influence.